Comparison of metal accumulation between ‘Artificial Mussel’ and natural mussels (Mytilus galloprovincialis) in marine environments - Gonzalez-Rey, Maria (2020)
The passive sampler called 'Artificial Mussel' (AM) developed by Wu et al. (2007) can provide a time-integrated estimate of metal concentrations in the marine environment, and offers a potential device to assess and compare metal concentration in different marine environments worldwide. The aim of this study was to compare metal accumulation on AM and natural mussel Mytilus galloprovincialis at three sites with different metal loads along the Portuguese coast for four months. M. galloprovincialis were placed in cages alongside AMs at each site. Samples were collected monthly and Cd, Cr, Cu, Pb, and Zn concentrations in whole soft tissues and AMs compared. For both Cu and Cd, the results were similar between AMs and natural mussels. Higher concentrations of Zn were observed in natural mussels, whereas the inverse was shown for Pb (about 10-fold higher). Our results showed that AMs are promising tools for assessing metal concentrations in marine environments.